Identification and characterization of Xenopus tropicalis common progenitors of Sertoli and peritubular myoid cell lineages - Tereza Tlapakova (Biology Open, 2016)
The origin of somatic cell lineages during testicular development is controversial in mammals. Employing basal amphibian tetrapod Xenopus tropicalis we established a cell culture derived from testes of juvenile male. Expression analysis showed transcription of some pluripotency genes and Sertoli cell, peritubular myoid cell and mesenchymal cell markers. Transcription of germline-specific genes was downregulated. Immunocytochemistry revealed that a majority of cells express vimentin and co-express Sox9 and smooth muscle α-actin (Sma), indicating the existence of a common progenitor of Sertoli and peritubular myoid cell lineages. Microinjection of transgenic, red fluorescent protein (RFP)-positive somatic testicular cells into the peritoneal cavity of X. tropicalis tadpoles resulted in cell deposits in heart, pronephros and intestine, and later in a strong proliferation and formation of cell-to-cell net growing through the tadpole body. Immunohistochemistry analysis of transplanted tadpoles showed a strong expression of vimentin in RFP-positive cells. No co-localization of Sox9 and Sma signals was observed during the first three weeks indicating their dedifferentiation to migratory-active mesenchymal cells recently described in human testicular biopsies.